The Effect of Blended Learning Model and Higher Order Thinking Skills on Students' Learning Achievement - Gunawan, Guntur; Sapri, Johanes; Hadiwinarto, Hadiwinarto; Yumiarty, Yuyun (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2022)
The traditional learning model makes students only spectators and listeners, so the learning process becomes passive. Limited time is also causing a lack of students' absorption of the material presented. The purpose of this study was to compare student learning outcomes that use a blended learning model and the traditional learning model. This study used a quasi-experimental approach with a nonequivalent factorial pretest-posttest control group design. The instruments to collect data included tests of higher-order thinking skills and learning achievement tests. The results of the study show that the blended learning model has a significant influence on student achievement in Islamic Religious Education subject. There is a sizable difference in student achievement between the experimental group and the control group. This research perhaps helps lecturers understand how to apply blended learning.